MOTIF MAGIS KAYANGAN CERITA RAKYAT RIAU (KAJIAN INTERTEKSTUAL) - Luki Aswar; Elmustian Elmustian; Syafrial Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study is titled Magical Motifs Kayangan of Riau Folklore (Intertextual Study). The background of this research is that the researchers want to see how the magical motifs of the sky consist of the main motifs of the angelic stories as well as the similarities and differences in the inner elements of the two folklore texts. The aim of this study is to describe the magical motifs of the folklore text of the legend of Putri Mambang Linau and Mahligai Keloyang (origin of the name Kelayang) from the main motifs of the Bidadari stories and similarities and differences in the intrinsic structure of the folklore text Legend of Putri Mambang Linau and Mahligai Keloyang (Originally Names) to describe Kelayang). This research is a descriptive qualitative research that describes and describes the results of the study. The data of this study are the folklore text of the legend of Putri Mambang Linau and Mahligai Keloyang (origin of the name Kelayang). Data obtained using the reading and recording method. Based on the results of the study, one found a magical motif in the form of angels, angelic cloths, hermitage, number of angels and kayangan. And the similarities and differences in the inner elements of both folklore texts.Key Words: intertextual, folklore, structural, magical motifs kayangan